2022
DOI: 10.1038/s43856-022-00124-5
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-resistant organisms establish reservoirs in new hospital built environments and are related to patient blood infection isolates

Abstract: Background Healthcare-associated infections due to antibiotic-resistant organisms pose an acute and rising threat to critically ill and immunocompromised patients. To evaluate reservoirs of antibiotic-resistant organisms as a source of transmission to patients, we interrogated isolates from environmental surfaces, patient feces, and patient blood infections from an established and a newly built intensive care unit. Methods We used selective culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 95 publications
(99 reference statements)
1
21
1
Order By: Relevance
“…Third, hospital water systems enable the "source-sink" dynamics of SMC populations 43 . Hospital sinks, particularly those located in ICUs, are increasingly identified as reservoirs of multidrug-resistant Pseudomonas and Enterobacterales, with most of the available studies focusing on identifying the origin of outbreaks or the impact of interventions to control bacterial transmission 5,6,[44][45][46] . The absence of long-term analysis of microbial populations with frequent and systematic sampling of patients and sinks during non-outbreak periods precludes the understanding of the transmission pathways of opportunistic pathogens and the ecology of microbial populations in the hospital-built environment.…”
Section: Discussionmentioning
confidence: 99%
“…Third, hospital water systems enable the "source-sink" dynamics of SMC populations 43 . Hospital sinks, particularly those located in ICUs, are increasingly identified as reservoirs of multidrug-resistant Pseudomonas and Enterobacterales, with most of the available studies focusing on identifying the origin of outbreaks or the impact of interventions to control bacterial transmission 5,6,[44][45][46] . The absence of long-term analysis of microbial populations with frequent and systematic sampling of patients and sinks during non-outbreak periods precludes the understanding of the transmission pathways of opportunistic pathogens and the ecology of microbial populations in the hospital-built environment.…”
Section: Discussionmentioning
confidence: 99%
“…Patient 27 is just such an example, but the lack of early sampling (2000-2010) and incomplete collection thereafter precludes a definitive answer. Indeed, other scenarios cannot be discounted, with a recent study showing sinks in a newly built ICU were already contaminated with an outbreak clone of P. aeruginosa before the arrival of the first patients 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Two studies reported S. maltophilia as a highly prevalent microorganism in high touch surfaces and hospital sinks, exceeding the prevalence of A. baumannii and P. aeruginosa [50,51]. Sink drains seemed to harbour S. maltophilia for several months, even in newly built ICU facilities [52]. This might explain the increasing prevalence of this microorganism in HCAIs.…”
Section: Text Of Reviewmentioning
confidence: 99%